Looking Back (Raton, New Mexico Raton Range, 1979)
Article on the costumes worn by the Kearny Entrada in 1955.
Master List item # 2
File location is in the Raton File Cabinet
Keywords: Teague, Myrtis; Local History; Costumes; Raton, New Mexico